Platelet-rich therapy in the treatment of patients with hip fractures: a single centre, parallel group, participant-blinded, randomised controlled trial. Issue 6 (25th June 2013) - Griffin, Xavier L; Achten, Juul; Parsons, Nick; Costa, Matt L
Abstract : Objective: To quantify and draw inferences on the clinical effectiveness of platelet-rich therapy in the management of patients with a typical osteoporotic fracture of the hip. Design: Single centre, parallel group, participant-blinded, randomised controlled trial. Setting: UK Major Trauma Centre. Participants: 200 of 315 eligible patients aged 65 years and over with any type of intracapsular fracture of the proximal femur. Patients were excluded if their fracture precluded internal fixation. Interventions: Participants underwent internal fixation of the fracture with cannulated screws and were randomly allocated to receive an injection of platelet-rich plasma into the fracture site or not. Main outcome measures: Failure of fixation within 12 months, defined as any revision surgery. Results: Primary outcome data were available for 82 of 101 and 78 of 99 participants allocated to test and control groups, respectively; the remainder died prior to final follow-up. There was an absolute risk reduction of 5.6% (95% CI −10.6% to 21.8%) favouring treatment with platelet-rich therapy (χ 2 test, p=0.569). An adjusted effect estimate from a logistic regression model was similar (OR=0.71, 95% CI 0.36 to 1.40, z test; p=0.325). There were no significant differences in any of the secondary outcome measures excepting length of stay favouring treatment with platelet-rich therapy (median difference 8 days, Mann-Whitney U test; p=0.03). The number and distribution of adverse events were similar. Estimated cumulative incidence functions for the competing events of death and revision demonstrated no evidence of a significant treatment effect (HR 0.895, 95% CI 0.533 to 1.504; p=0.680 in favour of platelet-rich therapy). Conclusions: No evidence of a difference in the risk of revision surgery within 1 year in participants treated with platelet-rich therapy compared with those not treated. However, we cannot definitively exclude a clinically meaningful difference. Trial registration: Current Controlled Trials, ISRCTN49197425, http://www.controlled-trials.com/ISRCTN49197425